ANALISIS BIBLIOMETRIK PENELITIAN PARIWISATA SYARIAH HALAL DI INDONESIA MELALUI DATABASE SCOPUS - Irfan Harmoko (Faculty of Islamic Economic and Business (FEBI), Sayyid Ali Rahmatullah State Islamic University (UIN SATU) Tulungagung, 2023)
The purpose of this research is to analyze the bibliometric characteristics and trends in scholarly publications on halal tourism in Indonesia based on the Scopus database. Data collection was conducted in March 2023, using the search keyword